(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: In spite of intensive antiviral and anti-inflammatory therapy, recovery is not always achieved in patients with stromal herpes keratitis (HK). Inflammatory host response and a complex immune defense system play a major role among the numerous factors involved in herpes simplex virus (HSV) reactivation from latency. Inter-Cellular Adhesion Molecule (ICAM-1) is best known for its role in mediating leukocyte adhesion to endothelial cells and guiding leukocytes across the vascular wall. This factor is considered as an inflammatoty biomarker. Given that signs of inflammation in recurrent stromal keratitis are not always clinically manifest, additional diagnostics is required for well-founded anti-inflammatory treatment decisions. Purpose: To assess the expression of ICAM-1 on blood lymphocytes in patients with primary stromal HK and patients experiencing one or more annual recurrences of stromal HK at different periods of disease. Material and Methods: Fifty-six patients (age, 20 to 60 years) who had been consulted and treated for stromal HK at the Department of Corneal Disorders and 27 systemically and ophthalmologically healthy controls (age, 20 to 64 years) were involved in the study. Of the 56 patients, 10 had primary HK with disease duration ? 6 months, and 46 had recurrent HK with disease duration ? 20 years. Individuals experiencing more than one recurrence annually were defined as those with frequent recurrences. Absolute and relative ICAM-1 expression on lymphocytes was examined. Immunohistochemical staining with monoclonal antibodies for ICAM-1 (CD-54) was performed. Results: The median and interquartile range of the absolute expression level of ICAM, and the mean (standard deviation) of the relative ICAM-1 expression on peripheral blood lymphocytes in controls were 113.3 cells/?L, 87-168 cells/?L, and 8.5 (2.0)%, respectively. Total patients with HSV keratitis exhibited significantly (4.0 times; p = 0.0001) higher absolute counts of peripheral blood lymphocytes expressing ICAM-1 (median, 450 cells/?L; interquartile range, 326-552 cells/?L) compared to controls. In patients in remission with recurrent stromal HK, the relative ICAM-1 expression did not depend on the frequency of recurrence and was 23.4 (4.0)%, which was 2.8 times higher than in controls (p = 0.000). Patients with active keratitis experiencing one recurrence annually had practically the same relative ICAM-1 expression as those experiencing more than one recurrence annually, with a mean value of 26.8 (4.6)%. This was 3.3 times higher than in controls (p = 0.000) and 15.8% higher than in patients in remission with recurrent HK (23.4 (4.1)%; p = 0.001). The relative ICAM-1 expression in patients with primary keratitis was 16% higher than in patients on remission, and there was no significant difference in this parameter between patients with primary keratitis and patients with active recurrent HK. Conclusion: The absolute and relative ICAM-1 expression on peripheral blood lymphocytes in patients with HSV keratitis was 4.0 times and 3.1 times, respectively, higher than in controls. The relative expression of ICAM on lymphocytes in patients with active recurrent disease and in patients with primary keratitis was 16% higher than in patients on remission.